Southern Cross River Agricultural Development Project Preparation Report - Federal Ministry of Agriculture Federal Department of Rural Development; Booker Agriculture International Limited London (Lagos, Nigeria : Devplan & Co.)
The reports highlighted number of advanced recommendations for food crops, with anticipated modifications to both the improved and advanced crop packages.
hza 13/02/2019
Loans
Keywords: Agriculture; Nigeria